ANALISIS FAKTOR PENENTU KUALITAS PEMBELAJARAN DALAM JARINGAN DI PERGURUAN TINGGI - Icha Yolanda; Suarman; Gani Haryana (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2022)
Online learning has actually become part of an alternative learning process at universities since the 90s. And since 2020 there has been a pandemic of COVID-19 conducing whole universities to do online learning. It is just that in the implementation, it causes many problems either from the lecturers or the students themselves. It is caused by many factors that determine as good as the learning or not will be carried out. Therefore, the study described in this article is designed to analyze the determinant factors and the influence on the quality of online learning. The study used 133students of Economics Education of FKIP Universitas Riau as respondents who were selected randomly. Data that were collected through questionnaires were Google form and analyzed by quantitative descriptive and statistical analysis by using Chi-square. Based on the results of data analysis, it was found that most of the respondents stated that the quality of online learning that had been carried out has been implemented procedurally based on the criteria for online learning. Furthermore, when it was seen from the determinant factor of the online learning quality, in fact, most of the respondents stated that either the facilities and infrastructure factors or lecturers and students factors, it has been adequate in descriptive analysis and as expected it was. After analyzing the statistical analysis, finally, the three factors also have an influence on the quality of online learning. Accordingly, it could be concluded that as good as online learning implementation or not were depending on the availability of facilities and infrastructure either provided by the universities or the students themselves. In addition, the lecturers who have qualifications and competencies and factors from students, especially those who were related to their enthusiasm and learning skills, technological literacy, communication, and collaboration, also determined the quality of online learning. Thus, based on the results of the study, it was recommended to improve the quality of online learning at universities, the facilities and infrastructure, especially for the facilities of network and LMS, the improvement of the lecturers’ competence in order to make the learning based on the demands of the 21st Century and RI of 4.0, and improve the students’ skills in online learning.